G-Protein-Coupled Receptor Kinase 2 Limits CCL21-Induced T Cell Migration via Phospholipase Cγ1 - Anahi Sanchez; Caitlin T. Winebrenner; Natalia Garcia; Brian Kaiser; Lyndsey Kilgore; Cesar I. Cardona; Daniel W. Bassuk; Mary E. Miller; Charles A. Bill; Laura A. Shannon; Brant M. Wagener; Amy Wagler; et al. (Receptors, 2025)
Background/Objectives: G protein-coupled receptors (GPCRs) can promote ligand-biased signaling, yet the mechanisms that promote bias are not well understood. We have shown that C-C Chemokine Ligand 19 (CCL19) and CCL21 promote ligand-biased internalization and signaling of C-C Chemokine Receptor 7 (CCR7) in T cells. The roles of GPCR kinases (GRKs) in regulating biased CCR7 internalization and biased signaling in T cells are unclear. GRK2 is a serine/threonine kinase that phosphorylates GPCRs in response to ligand binding and is recruited to the plasma membrane via its C-terminal pleckstrin homology domain to phosphatidylinositol 4,5-bisphosphate (PIP2). Methods: Human embryonic kidney cells (HEK293) transfected to express wild-type and mutant GRK2 and human CCR7, human T cell lines harboring heterozygous deletions of GRK2, and naïve primary T cells from GRK2 heterozygous (GRK2+/−) or GRK2f/f CD4-Cre mice were used to examine the effects of GRK2 on ligand-induced CCR7 signaling in T cells. We used flow cytometry to assay the effect of GRK2 on CCR7 internalization, Fluorescence Resonance Energy Transfer (FRET) to define the effect of GRK2 on CCR7 activation of Gαi isoforms and transwell migration assays to examine the effect of GRK2 on chemotaxis. Since chemotaxis via CCR7 is mediated by phospholipase Cγ1 (PLCγ1), Western blot assays were used to measure the effect of GRK2 during downstream signaling via phosphorylation of PLCγ1. Results: We found that following CCL19 binding, GRK2 promoted kinase-dependent CCR7 recruitment of arrestin-3, rapid CCR7 internalization and Gαi3 recruitment to CCR7. In contrast, following binding of CCL21 to CCR7, GRK2 slowed CCR7 internalization, induced recruitment of Gαi2 to the activated receptor, and promoted chemotaxis. Since we have shown that CCL21 promotes chemotaxis via PLCγ1, we examined the effect of GRK2 on PLCγ1 activation and found that GRK2 had no effect on CCL21-mediated PLCγ1 phosphorylation. Conclusions: GRK2 promotes differential signaling downstream of CCR7 activation by CCL19 and CCL21 and provides a model for biased signaling downstream of a GPCR driven by GRK2.